Nurcholish Madjid Weltanschauung: Educational Thought within the Framework of National Insight in Indonesia, 1971-2002 - Fakhrian, Luthfi Ridzki; Abrar, Abrar; Budiaman, Budiaman (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
Indonesia's civic and educational landscape has increasingly been fragmented by the rise of identity politics, ideological polarization, and the erosion of inclusive nationalism. Amidst this crisis, the educational thought of Nurcholish Madjid (Cak Nur) offers a transformative weltanschauung, a synthesis of Islamic ethics, national consciousness, and modern rationality. This study aims to critically investigate Madjid’s educational paradigm within the framework of wawasan kebangsaan (national insight), repositioning education not as dogmatic transmission but as civic moral formation. Employing a descriptive qualitative approach with critical historiographical methods, the research analyzes primary sources, including Madjid’s writings, interviews with key intellectuals, and institutional records, from 1971 to 2002. Anchored in the theories of Karl Mannheim and Antonio Gramsci, the study interprets Madjid as an organic intellectual whose vision is institutionalized through Universitas Paramadina, Madania School, and the Nurcholish Madjid Society. The findings reveal that Madjid’s inclusive educational praxis serves as both a moral critique and a civic alternative to ideological extremism in Indonesian schooling. His vision bridges Islam and Pancasila, integrates character education with democratic citizenship, and promotes pluralism as a religious imperative. The novelty of this research lies in contextualizing Madjid’s pedagogy as an instrument for rebuilding national character in postcolonial education, rather than reducing it to liberal theology. This paper contributes to global debates on religion, education, and civic ethics by proposing a homegrown Indonesian model that reconciles faith, diversity, and democracy. Madjid’s weltanschauung remains a viable blueprint for inclusive, ethical, and future oriented national education.